2022
DOI: 10.1029/2021gb007162
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of Space‐Time Variability in Global‐Ocean Dissolved Inorganic Carbon

Abstract: The inventory and variability of oceanic dissolved inorganic carbon (DIC) is driven by the interplay of physical, chemical, and biological processes. Quantifying the spatiotemporal variability of these drivers is crucial for a mechanistic understanding of the ocean carbon sink and its future trajectory. Here, we use the Estimating the Circulation and Climate of the Ocean‐Darwin ocean biogeochemistry state estimate to generate a global‐ocean, data‐constrained DIC budget and investigate how spatial and seasonal‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 119 publications
(191 reference statements)
4
21
0
Order By: Relevance
“…Further study to determine these uptake efficiencies, at a finer location sample resolution and ideally with model ensembles, are needed for optimal placement of OAE deployments. While our results give an overall picture and are indicative of the complexity, more sophisticated biogeochemistry models (e.g, Carroll et al, 2022) and higher-resolution regional coupled biogeophysical models (e.g., Sein et al, 2015;Wang et al, 2022) will be essential for simulation and deployment of real-world OAE projects.…”
Section: Discussionmentioning
confidence: 80%
“…Further study to determine these uptake efficiencies, at a finer location sample resolution and ideally with model ensembles, are needed for optimal placement of OAE deployments. While our results give an overall picture and are indicative of the complexity, more sophisticated biogeochemistry models (e.g, Carroll et al, 2022) and higher-resolution regional coupled biogeophysical models (e.g., Sein et al, 2015;Wang et al, 2022) will be essential for simulation and deployment of real-world OAE projects.…”
Section: Discussionmentioning
confidence: 80%
“…The other assimilation model used here is the ECCO-Darwin model (Carroll et al, 2020(Carroll et al, , 2022. This model features an ocean biogeochemistry and ecology model (Darwin) (Dutkiewicz et al, 2015) coupled to the ECCO data-assimilated physical circulation model (Forget et al, 2015;Zhang et al, 2018).…”
Section: Data Assimilation Modelsmentioning
confidence: 99%
“…Still, two recent papers found that the advective flux of DIC plays an important role in the carbon budget of the region (Carroll et al, 2022;Rosso et al, 2017). For example, Carroll et al (2022) find that the DIC tendency and interannual variability in their SIZ biome is dominated by net advection, although they do not show the contribution from the different advective components. Rosso et al (2017) do separate the advection into vertical, geostrophic and ageostrophic components, however, they compute their budget down to 650 m, which implicitly reduces the relative importance of Ekman transport (which only occurs in the top ∼80 m).…”
Section: Discussionmentioning
confidence: 97%
“…Comparison to model-based DIC budgets is also difficult since they are typically computed over fixed depths, and many models have seasonal variations in air-sea carbon fluxes that are inconsistent with observations (Mongwe et al, 2018). Still, two recent papers found that the advective flux of DIC plays an important role in the carbon budget of the region (Carroll et al, 2022;Rosso et al, 2017). For example, Carroll et al (2022) find that the DIC tendency and interannual variability in their SIZ biome is dominated by net advection, although they do not show the contribution from the different advective components.…”
Section: Discussionmentioning
confidence: 99%